STEM major’s decision to teach: examining teaching experiences in high-needs communities - Laura A. Edwards; Carla Gerberry (Disciplinary and Interdisciplinary Science Education Research)
Abstract A significant teacher shortage exists in the US, particularly in STEM teaching fields. Professionals in STEM fields make higher wages while teachers manage intense and challenging work conditions. Teacher dissatisfaction and shortage negatively impacts students’ learning outcomes. This paper examines how teacher self-efficacy developed for university science, technology, engineering, and mathematics (STEM) majors who participated in an internship and the shifts in their career path decisions to teaching STEM. Self-efficacy in potential teachers is key to future teachers’ perception of lowered levels of emotional exhaustion and higher job satisfaction influencing their transition to the teaching profession This study identifies how STEM major interns developed multiple sources of self-efficacy that transitioned half of the intern’s career choice to enter teaching STEM fields. Results reveal early exposure to teaching experiences and responsibilities influenced the decisions of the STEM majors to enter the teaching profession. This study contributes to teacher self- efficacy with insights into how early teaching experiences cultivate self-efficacy. Mastery teaching practice in authentic settings through the internships built self-efficacy. Additionally, relationships with peers as co-teaching assisted interns to develop their teaching self-efficacy. Findings point to lessons learned from curriculum and instruction in STEM teacher education that bridges research and practice for STEM education improvement and demonstrate teacher education programs benefit from early, authentic field-based experiences which motivate STEM majors’ desire to teach. It is crucial for future students to uncover how teacher-efficacy is developed for STEM teachers and their decisions to teach and persist in the teaching profession.